A digital information system for cultural landscapes: the case of Slender West Lake scenic area in Yangzhou, China - Chen Yang; Feng Han (Built Heritage, 2020)
Abstract The rapid development of digital technologies provides important opportunities for more effective cultural heritage conservation and management. While the concept of cultural landscape has been accepted by the academic community in the cultural heritage field for many years, the digital conservation of cultural landscapes still lacks pragmatic guidance. The aim of this article is to explore an approach for building a digital information system to support cultural landscape conservation and management. The Slender West Lake scenic area, a typical cultural landscape in China, was used as an instrumental case study. A geo-database was designed and established to integrate the information of the natural, cultural, tangible and intangible landscape features of Slender West Lake. The digital information system for cultural landscapes provides a more holistic, dynamic and specific cultural perspective on heritage for landscape conservators. The system provides comprehensive information support for heritage conservation, management and interpretation, which are not achievable with conventional tools. This article has expanded the cultural heritage theory by presenting a practical guide for the digital information management of cultural landscapes. The workflow for building a cultural landscape geo-database can be used as a reference for heritage projects in China and other countries.